Hacking digital ethics - Krieger, David J. (Anthem ethics of personal data collection, 2021)
This book is not a critique of digital ethics but rather a hack. It develops an exploit kit on the basis of state-of-the-art social theory and uses it to breach the insecure legacy system upon which the discourse of digital ethics is running. It exposes the bugs, the sloppy programming, and the false promises of current digital ethics, and, because it is an ethical hack, it redesigns digital ethics so that it can address the problems of the global network society.